O ácido giberélico promove a superação da dormência de sementes de arroz e a formação de plântulas anormais (Revista de Ciências Agroveterinárias, 2021)
Rice is one species that present dormancy after harvest and can be prolonged during seed storage. This work aimed to determine whether gibberellic acid (GA3) is an efficient promoter of dormancy-breaking in rice seeds and evaluate changes in biological structures via histochemistry. The cultivar used was SCS122 Miura submitted to 0 mg L-1, 500 mg L-1, and 1000 mg L-1 of GA3. Germination, viability, root, shoot and seedling length, starch optical microscopy, and quantification of total soluble sugars were performed. The use of 500 mg L-1 and 1000 mg L-1 of GA3 was efficient in dormancy-breaking rice seeds, reducing the percentage of dormant seeds to 4% and 1%, respectively. Despite lowering the dormancy percentage, the presence of GA3 causes an increase in the percentage of abnormal seedlings. Therefore, it cannot be recommended as a method of dormancy-breaking rice seeds at the concentrations used. Optical microscopy is efficient to verify that with the dormancy-breaking, the degradation of starch granules occurs, increasing the availability of total soluble sugars for the growth and development of seedlings.
Keywords: bioquímica; GA3; histoquímica; amido; açúcares solúveis totais